2005
DOI: 10.1016/j.jacc.2005.04.031
|View full text |Cite
|
Sign up to set email alerts
|

X-Sizer for Thrombectomy in Acute Myocardial Infarction Improves ST-Segment Resolution

Abstract: Reducing thrombus burden with X-Sizer before stenting leads to better myocardial reperfusion, as illustrated by a reduced risk of distal embolization and better ST-segment resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…In this regard, the use of a mechanical device for thrombus removal or trapping to improve clinical outcomes after p-PCI is attractive, and the efficacy of these devices has been tested in many clinical trials. Although some data, especially those regarding the use of distal protection devices, have failed to show clinical benefits due in part to patient and device selection [48][49][50][51][52][53] , many recent large-scale randomized trials have demonstrated significant improvements in myocardial perfusion 45,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] and the left ventricular function 64,65) in addition to reduced mortality 68) ( 69) . In addition, Burzotta et 70) .…”
Section: Thrombus Aspiration/distal Protection Therapy and Its Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the use of a mechanical device for thrombus removal or trapping to improve clinical outcomes after p-PCI is attractive, and the efficacy of these devices has been tested in many clinical trials. Although some data, especially those regarding the use of distal protection devices, have failed to show clinical benefits due in part to patient and device selection [48][49][50][51][52][53] , many recent large-scale randomized trials have demonstrated significant improvements in myocardial perfusion 45,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] and the left ventricular function 64,65) in addition to reduced mortality 68) ( 69) . In addition, Burzotta et 70) .…”
Section: Thrombus Aspiration/distal Protection Therapy and Its Efficacymentioning
confidence: 99%
“…Burzotta et al 58) (REMEDIA trial) Lefévre et al 59) (X AMINE ST trial) Silva-Orrego et al 60) (DEAR-MI study) Chevalier et al 61) (Export study) Sardella et al 62) (EXPIRA trial) Dudek et al 63) (PIHRATE trial) De Luca et al…”
Section: )unclassified
“…In the Randomized Evaluation of the Effect of Mechanical Reduction of Distal Embolization by Thrombus-Aspiration in Primary and Rescue Angioplasty (REMEDIA) trial, use of the manual aspiration Diver catheter (Invatec S.r.l., Brescia, Italy) before stent implantation was associated with improved ST-segment resolution and myocardial perfusion (19). Similarly, in the X-SIZER in Acute Myocardial Infarction Patients for Negligible Embolization and Optimal ST Resolution (X AMINE ST) trial, adjunctive thrombectomy with the X-Sizer device (eV3, Plymouth, Minnesota) led to better ST-segment resolution (20). In contrast, Kaltoft (21) found that patients who were treated with the Boston Scientific Rescue device (Mountain View, California) had significantly larger final infarct size at 30 days compared with patients treated with PCI alone.…”
Section: Acute Myocardial Infarction (Ami)mentioning
confidence: 97%
“…X-Sizer has two lumina: the outermost is connected to a vacuum bottle for debris aspiration (along with blood, collected into an in-line filter), while the innermost is for conventional guidewire passage. Helical thrombectomy is usually performed as a pre-stenting procedure, in order to reduce thrombus burden and improve the outcome of the procedure (Lefèvre et al 2005). Cutting and aspiration are designed to keep the risk of distal embolization low; however, complications like distal embolization, perforation and incomplete recanalization are reported in literature (C. H. Lee et al 2007).…”
Section: Helical Atherectomy/thrombectomymentioning
confidence: 99%